Material Volume Efficiency Study Using Tekla Structure and Revit Software - Suta, Tipala Prama; Hamdani, Hafiz; Ilmi, Muhammad Khalis (Newinera Publisher, 2025)
The development of technology in the construction industry drives the need for efficient and accurate planning methods, especially in material volume estimation which affects the budget and smooth running of the project. This study aims to compare the efficiency of material volume estimation between Two Building Information Modelling-Base software, namely Tekla Structure and Autodesk Revit. The study was conducted on the construction project of DPRD Building in North Lombok Regency. The method used includes modelling the main building structure such as foundations, sloofs, columns, beams, floor slabs, and roof structures in both software base on the same technical data. The estimated concrete volume and reinforcement weight data from each software were then analyzed quantitatively and compared with the conventional method. The results show that the concrete volume of the conventional method is about 7,8% larger than the results from Revit and Tekla. Meanwhile, the conventional method’s estimated reinforcement wight is up to 17,6% higher. Each software provides almost identical outputs, albeit with different approaches and interface. The efficiency is particularly noticeable in structural elements such as beams and floor slabs. These findings suggest that the use of BIM in the planning process can improve the accuracy of material estimation, minimize potential waste, and support more effective and accurate construction planning.